A more accurate definition of water characteristics in stone materials for an improved understanding and effective protection of cultural heritage from biodeterioration. (January 2022) - Li, Yong-Hui; Gu, Ji-Dong
Abstract: The water associated with cultural heritage materials is the most important factor before initiation microbial colonization and subsequent biodeterioration processes to occur. Since moisture or water in such materials is the key to life, a more refined characterization of water is needed to advance the basic understanding of the fundamental mechanisms, especially for the accurate assessment of bio-susceptibility or bio-receptibility of different materials. Water can be categorized to free, gravitational, capillary, and hygroscopic to account for the physical states and sorption strength with the materials. Material porosity or water-holding capacity are fundamental criteria used in characterization of various types of materials on a common ground and basis, but pore connectivity has been largely ignored and must be addressed to establish the methods for assessment and also its relationship to bio-colonization and biodeterioration. When a threshold value of water in the relevant physical categories is available, microbial life can colonize and establish colonies as biofilms on materials surfaces to carry out the biochemical reactions leading to biodeterioration, from appearance of discoloration to physical damage of the materials. Microbial destruction of inorganic materials is mainly carried out by the biochemical reactions through carbon, nitrogen and sulfur cycles. Among material porosity characteristics, available water and microorganisms, mobility and movement of soluble salts under wet and dry cycles have significant impact on the durability of materials. Uptake of soluble salts and supersaturated salts in water into materials can result in crystallization and mineral formation under evaporation condition to initiate the internal stress and cracks, which eventually result in surface delamination and damage. From an architecture design point of view, it is clear that management of water is a basic and important strategy to prevent development of microbial issues in the long-term protection of cultural heritage.